2014
DOI: 10.1111/dsu.12445
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Medical Student Preference for Simulation Models for Basic Dermatologic Surgery Skills: Simulation Platforms in Medical Education

Abstract: Preference data show that the pig foot model is preferred for teaching dermatologic surgical skills. These results re-affirm that the pig foot model is an effective, low-cost solution for training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…In the present literature, surgical training programs for medical students use a variety of models such as inanimate models, virtual reality, live animals, and human cadavers. 2,6 Human cadavers most closely approximate reality, but they are used sparsely owing to their high costs, limited availability, and the poor compliance of cadaveric tissue. Live animals represent a good teaching method, but the ethical issues, high costs, and need for specialized facilities limit their use.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the present literature, surgical training programs for medical students use a variety of models such as inanimate models, virtual reality, live animals, and human cadavers. 2,6 Human cadavers most closely approximate reality, but they are used sparsely owing to their high costs, limited availability, and the poor compliance of cadaveric tissue. Live animals represent a good teaching method, but the ethical issues, high costs, and need for specialized facilities limit their use.…”
Section: Discussionmentioning
confidence: 99%
“…It was a modified version of similar questionnaires used in previously published and validated studies. 2,3,[11][12][13] Basic Surgery Skills Training Package After review of similar previous studies, 14,15 each of the students who answered the preliminary questionnaire was anonymized by receiving a code. We then randomly selected 15 students from them (Research Randomizer, Version 4.0) for participation in the basic surgery skills training.…”
Section: Preliminary Surveymentioning
confidence: 99%
See 2 more Smart Citations
“…A survey of 157 medical students using pig's feet as a training tool on which to learn punch biopsies and simple interrupted suture techniques found that pig's feet were preferred above both synthetic skin and simulator models in 8 of 11 surveyed categories [10]. In addition to being the most economical platform, pig's feet were favored for the similarity they provided when compared to human skin [10]. Advances in surgical training platforms are making these products an increasingly attractive method for practicing the mechanics and techniques of surgical procedures.…”
Section: Teaching Modalitiesmentioning
confidence: 99%